1993
DOI: 10.1289/ehp.93101s6151
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of oxygenated fuels.

Abstract: The use of oxygenated fuels is anticipated to increase over the next decades. This paper reviews the toxicological and exposure information for methyl tertiary-butyl ether (MTBE), a fuel additive, and methanol, a replacement fuel, and discusses the possible health consequences of exposure of the general public to these compounds. For MTBE, the health effects information available is derived almost exclusively from rodent studies, and the exposure data are limited to a few measurements at some service stations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…More so, reports of human data are rare, and the scattered available research information may not be accessible to those at risk. Recently improved research techniques and exposure assessment measures, as well as reformulation of gasoline blends to avoid the harmful heavy metal additives and noxious constituents, such as lead and benzene [10], have improved the quantity and quality of data in research literature, and provide new and interesting results. Some studies provided already known facts, while others reported non-significant information, yet other studies reported that exposure led to adverse health effects, which has generated controversial scientific issues [11], suggesting the need for up-to-date review information on the workrelated ill health of gasoline service station attendants, globally.…”
Section: Pharmacodynamics and Systemic Toxicitymentioning
confidence: 99%
“…More so, reports of human data are rare, and the scattered available research information may not be accessible to those at risk. Recently improved research techniques and exposure assessment measures, as well as reformulation of gasoline blends to avoid the harmful heavy metal additives and noxious constituents, such as lead and benzene [10], have improved the quantity and quality of data in research literature, and provide new and interesting results. Some studies provided already known facts, while others reported non-significant information, yet other studies reported that exposure led to adverse health effects, which has generated controversial scientific issues [11], suggesting the need for up-to-date review information on the workrelated ill health of gasoline service station attendants, globally.…”
Section: Pharmacodynamics and Systemic Toxicitymentioning
confidence: 99%
“…Consequently this variable does not influence the alteration of HCT levels observed in traffic police. In literature has been observed an increase of HGB levels after chronic exposure to CH 3 OH and MTBE, used as octane enhancer in fuels 8) . In male students exposed to SO 2 , has been observed an increase in RBC, HGB and HCT levels 3) .…”
Section: Discussionmentioning
confidence: 99%
“…noise) and psycho-social stressors. Studies in literature have suggested that urban pollutants as lead (Pb) 1,2) , sulphur dioxide (SO 2 ) 3) , cobalt (Co) 4) , manganese (Mn) 5) , nikel (Ni) 6) , carbon monoxide (CO) 7) , methanol (CH 3 OH) and methyl-ter-butyl-ether (MTBE) 8) may cause alterations of red blood cells (RBC), hemoglobin (HGB) and hematocrit (HCT) values. The class of workers investigated in this study was constituted by traffic police of a big Italian city, for whom we have already studied the environmental and biological levels of some urban pollutants in previous researches.…”
Section: Introductionmentioning
confidence: 99%
“…Since fossil fuels are not a renewable source of energy, the need for promising alternatives such as alcohol has steadily increased in demand. Fuels heavily blended with alcohol have shown promise in the automotive industry [1]. In addition, methanol has been actively studied in fuel cells [2].…”
Section: Introductionmentioning
confidence: 99%